PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS LUMIO PADA MATERI PROFIL PEKERJAAN KELAS X SMKN 46 JAKARTA - Fazanur Salsabila; Roni Faslah; Eka Dewi Utari (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This research was motivated by low student learning motivation and the abstract nature of Job Profile material due to limited use of interactive visual media in class. This study aims to: (1) describe the stages of developing Lumio by SMART-based learning media on Job Profile material using the ADDIE model, (2) evaluate the academic validity of the media based on expert assessments, and (3) examine the operational practicality of the media based on student responses. The methodology used was Research and Development (R&D) applying the ADDIE development model (Analysis, Design, Development, Implementation, Evaluation). The trial subjects involved 36 grade X Office Administration students of SMK Negeri 46 Jakarta, divided into individual trial (3 students), small group trial (8 students), and field trial (25 students). The results showed that the average combined validity percentage reached 84.24%, categorized as "Very Valid". The average combined practicality rate reached 93.09%, categorized as "Very Practical" (comprising 92.03% in the small group trial and 94.15% in the field trial). Based on these findings, the Lumio by SMART-based learning media is concluded to be highly valid and practical for use as an interactive learning instrument on Job Profile material for grade X students at SMK Negeri 46 Jakarta.